Efektivitas Pakem dan Pembelajaran Mandiri Melalui Aplikasi Tiktok dalam Memproduksi Drama - Supardi, Chris Novika; Lina Siti Nurwahidah; Fakri Hamdani; Zainah Asmaniah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to find out the differences in drama learning outcomes through the use of the PAKEM model and Independent Learning with the TikTok application in producing drama videos by students. The background of this research was the learning process activities of SMAN 4 Tasikmalaya students in a pandemic situation which resulted in changes to the learning system. During the pandemic, learning was carried out in two parts, namely two JP through face-to-face, while the other 2 JP used the PJJ system. Based on this, researchers conducted research regarding the differences in the effectiveness of the PAKEM model and Mandifi Learning through the TikTok application. The method used in this study is a quantitative experimental method with a True Experimental design with the Posttest-Only Control Design type. The population is students of class XI SMAN 4 Tasikmalaya with a total of 70 people, while the sample used is 62 people divided into two classes. The research results obtained are as follows. First, the average score of class A students using the PAKEM model is 78.71. Second, the ability of the average value of class B students using the independent learning model is 76.67. Third, there is a significant difference in the effectiveness of the PAKEM model and the Independent learning model through the TikTok application in producing drama learning outcomes for class XI students of SMAN 4 Tasikmalaya using the t test.